TECHNOLOGIZATION OF THE TARBIУA JАRАONI IN MАKTАB READERS - Sаidnаzаrovа Gulshodа Fаrxаdovnа; Bаbауаzovа Irodа Rаximboу qizi (Bright Mind Publishing, 2026)
The article discusses the problems of educational technology, methods of achieving results by ensuring the achievement of the goal of the educational process through the development of the personality of the learner, and methods of organizing lessons using the most popular technologies in the organization of education. Innovative technologies allow for individualized education for children, taking into account the individual needs and capabilities of each child. Innovative technologies also contribute to the development of digital literacy skills and the preparation of primary school students for work in the modern information society.
Keywords: Educational technology, Forms of education, Educational functions, Forms of educational work, Modern pedagogical technologies.